Planning with all your senses - learning to cooperate on a regional scale. - Stein, Ursula (TH Zürich, ORL-Institut, 2005)
Der Beitrag gibt einen Einblick in die regionale Zusammenarbeit in Deutschland am Beispiel der Region Bonn/Rhein-Sieg/Ahrweiler, die nach dem Hauptstadtbeschluss erfolgreich die Restrukturierung der wirtschaftlichen Grundlagen durch die Entwicklung neuartiger Planungsformen betrieben hat und am Beispiel des "Regionalparks Saar", einem der beteiligten Regionen am SAUL-Projekt der EU, das den Wert sozial relevanter Freiräume in Ballungsgebieten für eine starke Wirtschaft, soziales Gleichgewicht und nachhaltige Entwicklung in den Mittelpunkt stellt. Hinzu kommt die Beschäftigung mit der Funktion der Raumplanung für die regionale Identität, mit partnerschaftlicher Planung und dem Ansatz der "Lernenden Region". Der Beitrag arbeitet die Unterschiede von regionalen und lokalen Planungsprozessen heraus und formuliert sie in grundsätzlichen Thesen. Die Fallstudien belegen die Erfahrung und den Rat einer "Planung mit allen Sinnen". oc/difu

"Planning with all your senses" is an experience as well as advice. The paper is based on the hypothesis that the stimulation of the basic senses and an appeal to beauty and emotions may contribute a great deal to the output and outcome of regional governance. This also helps learning, which is essential in planning in the context of dynamic urban landscapes. Therefore, taking the human senses as well as learning processes into account should be a part of creative governance. The paper explores two cases of facilitation of regional cooperation in Germany. The region of Bonn/Rhein-Sieg/Ahrweiler has - after the German capital was moved to Berlin in the 1990s - successfully combined the restructuring of the region's economic basis with the development of new regional planning procedures. The planning and implementation of the first part of the "Regionalpark Saar" was a creative process of cooperation using the "low impact" philosophy developed by the SAUL network. The first part of the paper recalls some basic facts that have to be taken into account when thinking about planning in the context of governance. In part two, a set of basic rules for facilitation on a regional level will be spelled out, because some characteristics are different from working at the urban level. These basic rules will be illustrated in two ease studies; one from the Bonn region and one from the Saarland, which will lead to the conclusions about "planning with all your senses". difu
Keywords: Regionalplanung; Kooperation; Partizipation; Planungstheorie; Strukturwandel; Freiraumplanung; Fallstudie; Projekt; Regionalpark; Bürgerbeteiligung